KAJIAN PEMANFAATAN RUANG DI KAWASAN TEPIAN DANAU BERATAN, BALI - Gusti Ayu Putu Arista Ardianti; Wahyudi Arimbawa; I Gusti Putu Anindya Putra (Pranatacara Bhumandala: Jurnal Riset Planologi, 2022)
The purpose of this study is to determine the spatial use of the Lake Beratan area and to analyze the suitability of its designation with the spatial plan of Tabanan Regency. This was studied based on the existence of various activities on the shores of the lake, namely the existence of a sacred area and also a tourist area, as well as local community agricultural land. The method used in this study is a qualitative method to produce descriptive data in the form of written or spoken words from the observed person or object. Data analysis used in this research is descriptive analysis and overlay analysis. Observations were made to see directly the use of space on the shores of Lake Beratan. From the results of this space utilization it can be concluded that the existing space utilization is dominated by paddy fields. From the results of the overlay, it shows that the use of space in the research location is in accordance with the regional spatial planning and the conversion of functions in the research area has obtained the KKPR permit.